أثر حجم الإقتصاد الموازي على الإيرادات العادية في الجزائر خلال الفترة 1990 - 2017 - حاقة, حنان; لبزة, هشام (جامعة الوادي - University of Eloued, 2019)
ملخص: هدفت الدراسة إلى قياس وتحليل أثر حجم الإقتصاد الموازي على الإيرادات العادية في الجزائر بإستخدام بيانات سنوية خلال الفترة 1990 -2017. وتحليل بيانات سنوية بإستخدام نماذج مختارة لتقدير مدى تأثير حجم الاقتصاد الموازي على الإيرادات العادية (نموذج الإنحدار الخطي البسيط، نماذج غير الخطية، نموذج التأخيرات)، ويستند هذا القياس والتحليل إلى نموذج التأخيرات أو الإبطاء كأفضل نموذج. وذلك بالإستعانة على برنامج القياس الاقتصادي EViews9 وخلُصت الدراسة إلى أن : - حجم الإقتصاد الموازي في الفترة الحالية يمارس تأثيرا إيجابياً على الإيرادات العادية في الفترة الحالية وهذا غير مطابق للنظرية للإقتصادية. - كما توجد علاقة عكسية بين حجم الإقتصاد الموازي المبطئ لفترة واحدة وحجم الإيرادات العادية، فكلما زاد حجم الإقتصاد الموازي المبطئ لفترة واحدة كلما قلت الإيرادات العادية. وهذا وفقا لما دلت عليه الإشارة السالبة، وهذه النتيجة أيضاً جاءت موافقة للنظرية الإقتصادية. الكلمات المفتاحية: الإقتصاد الموازي، الإيرادات العادية، النموذج الخطي البسيط ، النموذج غير الخطي، نماذج الإبطاء. تصنيفJEL :؛ C52.E26.H2 Abstract The purpose of this study is to measure and analyze the impact of the size of the shadow economy on regular income in Algeria using annual data for the period 1990-2017. Annual data analysis using selected models to assess the impact of the size of the shadow economy on regular income (simple linear regression, nonlinear models, model delays). This is based on the measurement and analysis model of delays or delay as the best model. Drawing on economic measurement program EViews9. The study concluded that:-the size of the shadow economy in the current exercise a positive influence on regular income in the current period, this shoddy economic theory. -There is an inverse relationship between the size of the shadow economy the slow for a single size of regular income, the larger the size of the shadow economy the slow one term less regular income. This is in accordance with evidenced that negative, this result also came with economic theory. Key words: the shadow economy, ordinary revenues, the simple linear model, non-linear model, models the delay . Classification JEL:c52; E26; H2
The impact of the size of the parallel economy on ordinary revenues in Algeria During the period 1990-2017
مقال
Keywords: الإقتصاد الموازي، الإيرادات العادية، النموذج الخطي البسيط ، النموذج غير الخطي، نماذج الإبطاء.; the shadow economy, ordinary revenues, the simple linear model, non-linear model, models the delay